2017
DOI: 10.3390/nu9030294
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association of Plasma Chromium Levels with Newly Diagnosed Type 2 Diabetes: A Case-Control Study

Abstract: Chromium has long been known as an enhancer of insulin action. However, the role of chromium in the development of type 2 diabetes mellitus (T2DM) in humans remains controversial. The current study aimed to examine the associations of plasma chromium levels with T2DM and pre-diabetes mellitus (pre-DM). We conducted a case-control study involving 1471 patients with newly diagnosed T2DM, 682 individuals with newly diagnosed pre-DM, and 2290 individuals with normal glucose tolerance in a Chinese population from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 39 publications
3
20
2
Order By: Relevance
“…Although the pathogenesis of MetS remains unclear, recent interest has focused on the possible involvement of insulin resistance as a linking factor [28]. Coincident with this, our previous study has elaborated the inverse association between plasma chromium concentrations and type 2 diabetes mellitus and pre-diabetes mellitus in a case-control study [12]. In addition, evidences in animal and in vitro studies supported the association as well.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Although the pathogenesis of MetS remains unclear, recent interest has focused on the possible involvement of insulin resistance as a linking factor [28]. Coincident with this, our previous study has elaborated the inverse association between plasma chromium concentrations and type 2 diabetes mellitus and pre-diabetes mellitus in a case-control study [12]. In addition, evidences in animal and in vitro studies supported the association as well.…”
Section: Discussionmentioning
confidence: 55%
“…There was another case-control study suggesting an association between low chromium levels and increased risk of nonfatal myocardial infarction [11]. Besides, our previous study found that plasma chromium concentrations were inversely associated with type 2 diabetes mellitus and pre-diabetes mellitus [12].…”
Section: Introductionmentioning
confidence: 91%
“…Coincident with this, the association of plasma chromium with high blood glucose was the strongest among the components of MetS in this study. Our previous study has elaborated the inverse association between plasma chromium concentrations and type 2 diabetes mellitus and pre-diabetes mellitus in a case-control study [12].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, our previous study found that plasma chromium concentrations were inversely associated with type 2 diabetes mellitus and pre-diabetes mellitus [12]. Yet some studies did not support the inverse relationship between chromium and MetS [13,14].…”
Section: Introductionmentioning
confidence: 90%
“…As an adjunctive treatment method for T2DM, Chinese herbal medicines have been used in clinical practice for many years [ 17 19 ]. Two studies also indicated that plasma chromium concentrations were inversely associated with T2DM and pre-DM in Chinese adults [ 20 , 21 ]. Relevant systematic reviews have shown that chromium can reduce FBG [ 22 ].…”
Section: Discussionmentioning
confidence: 99%